2023
DOI: 10.3390/insects14020134
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis Provides New Insights into the Molecular Basis of Thermal-Induced Parthenogenesis in Silkworm (Bombyx mori)

Abstract: Artificial parthenogenetic induction via thermal stimuli in silkworm is an important technique that has been used in sericultural production. However, the molecular mechanism underlying it remains largely unknown. We have created a fully parthenogenetic line (PL) with more than 85% occurrence and 80% hatching rate via hot water treatment and genetic selection, while the parent amphigenetic line (AL) has less than 30% pigmentation rate and less than 1% hatching rate when undergoing the same treatment. Here, iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…We identified 97,996 known spectra, 66,953 unique spectra, 12,530 peptides, 9568 unique peptides, and 3898 proteins, respectively (Table S1 and Figure S1). Based on previous studies [38], differentially expressed proteins (DEPs) were defined based on a 1.2-1.5 fold change threshold. Among the proteins, only one protein in two or three replicates Note: *, **, and *** mean that the difference between the two groups is less than 0.05 (p < 0.05), 0.01 (p < 0.01), 0.001 (p < 0.001), respectively; ns means that the difference between the two groups is more than 0.05.…”
Section: Results Of Itraq Analysis and Differential Protein Screening...mentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 97,996 known spectra, 66,953 unique spectra, 12,530 peptides, 9568 unique peptides, and 3898 proteins, respectively (Table S1 and Figure S1). Based on previous studies [38], differentially expressed proteins (DEPs) were defined based on a 1.2-1.5 fold change threshold. Among the proteins, only one protein in two or three replicates Note: *, **, and *** mean that the difference between the two groups is less than 0.05 (p < 0.05), 0.01 (p < 0.01), 0.001 (p < 0.001), respectively; ns means that the difference between the two groups is more than 0.05.…”
Section: Results Of Itraq Analysis and Differential Protein Screening...mentioning
confidence: 99%
“…We identified 97,996 known spectra, 66,953 unique spectra, 12,530 peptides, 9568 unique peptides, and 3898 proteins, respectively (Table S1 and Figure S1). Based on previous studies [38], differentially expressed proteins (DEPs) were defined based on a 1.2-1.5 fold change threshold. Among the proteins, only one protein in two or three replicates with fold changes ≥1.2 was defined up-regulated or ≤0.83 as down-regulated.…”
Section: Results Of Itraq Analysis and Differential Protein Screening...mentioning
confidence: 99%
“…In insects, the chorion has the essential function of protecting the embryo from external agents during development while allowing gas exchange for respiration [72]. In B. mori, an earlier study showed that heat shock treatment to pupae resulted in upregulation of vitellogenin expression in both the ovary and fat body [73], and a recent study further demonstrated that thermal induction induced upregulation of chorion class A and B proteins [74]. The upregulation of these genes indicates their role in reproductive protection upon heat shock.…”
Section: Discussionmentioning
confidence: 99%